Вплив тривалості гарячого пресування на кінетику усадки і структуру алмазовмісних композитів на основі металевих матриць - Бондаренко, М.О.; Коростишевський, Д.Л.; Супрун, М.В.; Мечник, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Influence of duration of hot pressing on kinetics of contraction of structuring in system diamond-Fe-Cu-Ni-Sn-CrB2 is investigated. It is proved, that optimization p-T-t hot pressing conditions allows receiving composites with necessary properties.